2022
DOI: 10.3390/su141811297
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Variables Affecting the Growth of the Tourist Sector in Guizhou Province

Abstract: The tourist industry is consistent with the new development paradigm and plays a crucial role in regional economic growth. At the same time, several areas of China have developed tourism as a vital industrial pillar. Analysing and examining the elements that affect the tourist industry in this setting has significant theoretical and practical implications. The dependent variable for this study is the tourist income for Guizhou Province from 2006 to 2019. A total of Eight variables are chosen as independent var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Based on the spatial and temporal evolution characteristics of museums in Shandong Province, this paper refers to the research results of other scholars [41][42][43][44] , considers multiple factors to construct a theoretical framework of economy-society-government-tourism-culture, and selects ve categories and fourteen indicators as explanatory variables and the number of museums as explanatory variables. The data from 2020 were selected for the analysis because some indicators of the latest year were not representative due to the impact of COVID-19.…”
Section: In Uencing Factors Of the Spatial Distribution Of Museumsmentioning
confidence: 99%
“…Based on the spatial and temporal evolution characteristics of museums in Shandong Province, this paper refers to the research results of other scholars [41][42][43][44] , considers multiple factors to construct a theoretical framework of economy-society-government-tourism-culture, and selects ve categories and fourteen indicators as explanatory variables and the number of museums as explanatory variables. The data from 2020 were selected for the analysis because some indicators of the latest year were not representative due to the impact of COVID-19.…”
Section: In Uencing Factors Of the Spatial Distribution Of Museumsmentioning
confidence: 99%
“…In addition, Konstantakopoulou found that the health quality of the host country had a significant impact on international tourism revenue [ 10 ]. Zhang et al believed that transportation accessibility, tourism infrastructure construction, foreign direct investment and the number of employees in the tertiary industry were all important factors that affected the tourism development of Guizhou Province [ 11 ]. Many scholars believed that regional tourism resource endowment is also the main factor affecting tourism development [ 12 , 13 , 14 ].…”
Section: Literature Reviewmentioning
confidence: 99%